IMPLEMENTASI NILAI-NILAI AGAMA ISLAM DALAM MENUMBUHKAN RESILIENSI SISWA MELALUI PEMBELAJARAN PAI DI SMPN 3 JOMBANG - Fauziah, Fifin; Umam , Khoirul; Said, Ali (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2024)
Education as a means of character building for students is very important for students in living this life. One of the most important characters to be developed in students is resilience. Resilience is the ability of students to rise from problems. Teachers play a rolein fostering Islamic religious values as an effort to increase resilience through education. SMP Negeri 3 Jombang is a school that greatly emphasizes its Islamic culture. This can affect students' attitudes when facing difficult situations. There are 3 focuses studied in this study: 1) To describe Islamic religious values in SMP Negeri 3 Jombang, 2) To describe the application of Islamic religious values in fostering student resilience through Islamic Religious Education learning in SMP Negeri 3 Jombang, 3) To describe the supporting and inhibiting factors for the implementation of Islamic religious values in fostering student resilience through Islamic Religious Education learning in SMP Negeri 3 Jombang. This study uses a descriptive qualitative approach with a case study research type. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used are data reduction, data display, and data verification. The researcher achieved the following research results: 1) Islamic religious values in SMP Negeri 3 Jombang that are instilled in students include material on ikhtiar, tawakal, sabar, and Ikhlas. 2) The implementation of Islamic religious values in SMP Negeri 3 Jombang is carried out in several ways, namely: Through Teaching, Through Role Modeling, Through Habits, Through Advice, Through Rule Enforcement, and Making Students Independent. 3) Supporting factors: good collaboration between teachers and parents, adequate facilities, many competent PAI teachers, and a supportive school environment. While the inhibiting factors: lack of student motivation and lack of good examples from parents.